Local cold exposure of the hands from cryosectioning work in histopathological and toxicological laboratories: signs and symptoms of peripheral neuropathy and Raynaud's phenomenon. Issue 4 (April 1996) - Wieslander, G; Norbäck, D; Edling, C
Abstract : OBJECTIVES: To study relations between cryosectioning work, skin temperature, early signs of neuropathy in the hands, and vasospastic and neurological symptoms. Microtome work is carried out at histological and toxicological laboratories all over the world. It implicates local cold exposure of -20 degrees C on the hands of exposed laboratory technicians. METHODS: Thirty nine laboratory technicians who use microtomes at the preclinical and clinical laboratories at the University of Uppsala, Sweden were studied. An equal number of nonexposed laboratory technicians served as controls, matched for workplace, sex, age, and smoking habits. Information on symptoms, type of work, and personal factors were assessed by means of a self administered questionnaire. Two point discrimination ability was tested, and vibration perception threshholds were measured for both hands by a bio-thesiometer. Also, skin temperature was measured during cryosectioning work in those 15 technicians performing cryosectioning work during the study period. RESULTS: Most laboratory technicians did not use any gloves during cryosectioning work, and direct contact with frozen materials sometimes occurred and resulted in a rapid cooling of the skin. In six of 15 exposed subjects (40%), the mean skin temperature during microtome work was below 20 degrees C. A later rise in skin temperature, due to a compensatory vasodilation, was found in two subjects. The group exposed to cold had signs of early neuropathy on the right hand, indicated both by vibrametry and two point discrimination test. Significant work related differences in clinical signs within the group exposed to cold was also found. No differences between exposed and nonexposed people were found for symptoms of Raynaud's phenomenon, numbness, or musculosceletal complaints. CONCLUSION: Our study shows that cryosectioning laboratory work may cause adverse health effects–for example, peripheral neuropathy–and measures should be taken to protect the hands from the local cold exposure.